Code Mixing Used By Vlogger “ Tasya Farasya” On TikTok Videos - Ni Kadek Ayu Adinda Pratiwi; I Dewa Ayu Devi Maharani Santika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the phenomenon of code-mixing in the TikTok videos of beauty vlogger Tasya Farasya. It aims to identify the types and reasons for code-mixing using the framework proposed by Hoffman (1991), which includes three types: intra-sentential, intra-lexical, and involving a change of pronunciation. The research uses a qualitative descriptive method to analyze 6 utterances selected from 4 of her TikTok videos posted between December 2024 and March 2025. The findings reveal that intra-sentential code-mixing appears in 3 utterances (50%), intra-lexical code-mixing also occurs in 2 utterances (33.33%), while code-mixing involving a change of pronunciation is found in 1 utterance (16.67%). These findings indicate that intra-sentential and intra-lexical code-mixing are used with equal frequency, whereas pronunciation related code-mixing is less common. This study examines the phenomenon of code-mixing in the TikTok videos of beauty vlogger Tasya Farasya. A qualitative descriptive method was employed to provide a systematic and in-depth account of the forms of code-mixing and the contexts in which they occur in real social media interactions. The findings suggest that code-mixing in Tasya Farasya’s content represents a strategic linguistic choice a deliberate use of mixed language to achieve specific communicative purposes, such as emphasizing meaning, fostering closeness with the audience, projecting a modern image, and enhancing the overall appeal of the content. Furthermore, this study highlights how English is integrated into Indonesian social media discourse, particularly in the beauty and lifestyle domain.